ANALISIS RESEPSI KHALAYAK TERHADAP NILAI MASKULINITAS BARU DALAM IKLAN KOSMETIK KHUSUS PRIA (The Commercium, 2023)
The new masculinity is a hegemonic concept of masculinity and can be adjusted based on the context of the times. The new masculinity has abandoned the old masculine values that many men consider to restrain and compartmentalize men and women. Metrosexual is one of the new concepts of masculinity that is popular and widely embraced by today's society , especially urban and metropolitan communities. Men’s cosmetic advertisements display metrosexual values with the aim of increasing their sales, because the metrosexual market has been formed. This study uses the Stuart Hall reception analysis method and using in-depth interviews as data collection techniques. The results showed that there were two categories of acceptance of media messages, namely 1) dominant category, with two informants having three main acceptance points, 2) negotiation category, with four informants having two main negotiation points. In addition to these two categories, two points of same acceptance were found in common with all informants, namely, 1) maintaining appearance is a necessity for every man today, and 2) the appearance of a metrosexual model as a new masculinity value in advertisements can increase public awareness about new masculinity value. Future research can examine what factors can influence audience acceptance of messages potrayed by the media.